Analisis Pengaruh Harmonisa terhadap Rugi-Rugi Daya pada Sistem Tegangan Rendah dan Transformator GR088 di Penyulang Menjangan - Afif, Salim; Sukerayasa, I W.; Ariastina, W. G. (Jurnal SPEKTRUM, 2018)
Menjangan feeder is a medium-voltage network system which distributes electricity throughout Gilimanuk and some areas in Buleleng. It has 69 distribution substations, which one of them, substation GR088, contributes to the highest value of the total harmonic distortion (THDi). In this research, the effect of harmonic distortions on losses at low voltage system of substation GR088 will be evaluated.The method used in this study is direct measurement of harmonic distortions at each low-voltage costumer whose electricity is generated by substation GR088 at Menjangan Feeder. Software is also used to perform harmonic load flow analysis and simulations. The total value of losses on transformer and low voltage system of substation GR088 Menjangan feeder, in a no-harmonic condition is 1481,7 Watt. On under-harmonic condition, the total value of losses is 1552,5 Watt. Therefore there is a 70,8 Watt difference between the two conditions. At this case, beside the heat created by the harmonic distortion that can affect the performance of transformers, it also cause a quite great value of losses, which is 1,7 kWh per day, or approximately 620 kWh per year. It means the harmonic distortion in substation GR088 can cause PT PLN (Persero) lose Rp.910.018,8 per year.